The bioavailability and pharmacokinetics of morphine after intravenous, oral and buccal administration in healthy volunteers. - Hoskin, P J (1989)
1. The absolute bioavailability of morphine from oral aqueous solution, a controlled release oral tablet (MST-Continus) and a controlled release buccal tablet has been investigated in six healthy volunteers. 2. Analysis of plasma samples for morphine and its active metabolite morphine-6-glucuronide (M6G) was by means of a differential radioimmunoassay technique. Absolute bioavailability for morphine was estimated to be 23.9% after oral solution, 22.4% after MST-Continus and 18.7% after the buccal tablet. Maximum plasma morphine concentrations were seen at 45 min (oral solution), 2.5 h (MST) and 6 h (buccal). 3. There was no difference in the amount of M6G appearing in plasma after intravenous, oral or buccal administration but the mean ratio of AUCs for M6G: morphine in plasma after intravenous morphine was 2 : 1 compared with 11 : 1 after oral and buccal morphine.